Unsur Budaya Dalam Cerita Film Cakra Buana Karya Sutradara Massimo Burhanuddin - Dwiyanti, Revi; Suherman, Agus (LOKABASA, 2019)
This research is motivated by the lack of research on film that uses Sundanese language and cultural settings. This study aims to describe the cultural elements that exist in the Cakra Buana film story. The method used in this research is descriptive analysis with document study techniques in the form of artwork. The data source in this study is the story of the film Cakra Buana by director Massimo Burhanuddin. The results of the study include 7 cultural elements, including: language, this film uses Sundanese language and undak usuk basa, knowledge systems are divided based on knowledge about nature and social, social organizations include government systems, how to replace leaders and designations of kinship, technological systems including tools, food, clothing, houses and means of transportation, the livelihood system that is farming, the religious system is still influenced by Hinduism and Buddhism because it uses the word "Sang Hyang" in mentioning the name of God, and there are 2 arts in this film namely music and art motion (traditional dance).AbstrakPenelitian ini dilatarbelakangi oleh kurangnya penelitian tentang perfilman yang menggunakan bahasa dan latar budaya Sunda. Penelitian ini bertujuan untuk mendeskripsikan unsur budaya yang ada dalam cerita film Cakra Buana. Metode yang digunakan dalam penelitian ini adalah deskriptif analisis dengan teknik studi dokumen yang berupa karya seni. Sumber data dalam penelitian ini yaitu cerita film Cakra Buana karya sutradara Massimo Burhanuddin. Hasil penelitian meliputi 7 unsur budaya, diantaranya: bahasa, film ini menggunakan bahasa Sunda serta menggunakan undak usuk basa, sistem pengetahuan dibagi berdasarkan pengetahuan tentang alam dan sosial, organisasi sosial meliputi sistem pemerintahan, cara mengganti pemimpin dan sebutan kekerabatan, sistem teknologi diantaranya perkakas, makanan, pakaian, rumah dan alat transportasi, sistem mata pencahariannya yaitu bercocok tanam, sistem religinya masih ada pengaruh dari ajaran Hindu dan Buddha karena menggunakan kata â€œSang Hyangâ€ dalam menyebutkan nama Tuhan, dan kesenian dalam film ini ada 2 yaitu seni musik dan seni gerak.